Letters from Early Career Academics: the Physical Education and Sport Pedagogy field of play. Issue 1 (2nd January 2017) - Alfrey, Laura; Enright, Eimear; Rynne, Steven
Abstract : Taking our lead from Rainer Maria Rilke's (1929) 'Letters to a Young Poet', our broader project aimed to create a space for dialogue and intergenerational learning between Physical Education and Sport Pedagogy (PESP) Early Career Academics (ECAs) and members of the PESP professoriate. This paper focuses specifically on the experiences of PESP ECAs. We draw upon narratives of thirty ECAs from nine different countries to gain insight into the experiences, joys, challenges and ambitions they associate with being and becoming a PESP academic. A narrative analysis of the data generated by the ECAs was undertaken. The analysis aimed to be holistic in nature, interested in form and content: both the told (the content) and the telling (how it was told). We initially focused our analysis using the six dimensions of narrative (characters, setting, events, audience, causal relations and themes). Bourdieu's socio-analytical toolkit complemented our narrative analysis and helped us move beyond the personal narratives by linking them to the broader social practices, relations and structures of the various settings or fields (PESP, university, family) within which the participants function. The findings suggest that many ECAs are experiencing crises of habitus, as they work to suppress ethical dispositions and values and adjust to 'the rules' that universities increasingly play by. Our discussion engages with the affective costs of playing by these rules, and recruits Bourdieu's notion of 'reflexive vigilance' to advocate for ongoing critical analysis of how power operates in the various field which academics inhabit.